Opioid use and harms associated with a sustained-release tapentadol formulation: a postmarketing study protocol - Peacock, Amy (BMJ Open, 2018)
INTRODUCTION: It has been argued that tapentadol may pharmacologically have lower abuse potential than other pharmaceutical opioids currently available. However, there has been no comprehensive triangulation of data regarding use and harms associated with this formulation. A sustained-release formulation (SRF) of tapentadol (Palexia) was released in Australia in 2011 and listed for public subsidy in 2013. We summarise here the methods of a postmarketing study which will measure postintroduction: (1) population level availability, (2) extramedical use and diversion, (3) attractiveness for extramedical use and (4) associated harms, of tapentadol compared against other pharmaceutical opioids. METHODS AND ANALYSIS: We evaluated key sources on pharmaceutical use and harms in Australia. This review indicateddata from four sources that disaggregate pharmaceutical opioid formulations and capture tapentadol SRF could be triangulated. These data sources comprised: (1) national pharmaceutical opioid community sales data from 2011 to 2017, (2) national pharmaceutical opioid poisonings reported to Poison Information Centres (PICs) from 2011 to 2017, (3) number of vendors on online marketplaces listing pharmaceutical opioids for sale and (4) data on pharmaceutical opioid extramedical use, attractiveness and harms from interviews with people who regularly inject drugs in Australia. ETHICS AND DISSEMINATION: Ethics approval is not required for use of pharmaceutical sales data. Ethics approval has been obtained for use of national pharmaceutical opioid poisonings reported to PICs (LNR/16/SCHN/44) and for use of online marketplace data and interview data from people who inject drugs (HC12086). Key findings will be published mid-2018 in a peer-reviewed academic journal, and presented at various conferences and professional meetings.